KRISIS DAN KOMUNIKASI KEPEMIMPINAN PUBLIK: ANALISIS FRAMING MEDIA SOSIAL KEPALA DAERAH DI INDONESIA PADA MASA PANDEMI COVID-19 - Rahmanto, Andre Noevi; Naini, Albert Muhammad Isrun; Priliantini, Anjang; Hendriyani, Christina Tri; Anshori, Mahfud (Interaksi: Jurnal Ilmu Komunikasi, 2022)
Public leaders have a significant role in overcoming the crisis caused by the COVID-19 pandemic. The communication process delivered by public leaders is the spearhead of handling global and local pandemics. Public leaders have different communication patterns in conveying their messages. This study seeks to determine the communication efforts made by community leaders in overcoming the COVID-19 pandemic. The method used in this research is Framing Analysis by Robert N. Entman. Researchers analyzed all news based on problem definitions, diagnosed causes, and made moral judgments and treatment recommendations on the social media of Ganjar Pranowo, head of the Central Java region. The research period during the pandemic is from March to May 2020. The results obtained by researchers are that regional heads are community leaders who have the authority to make all decisions. The leadership communication style used by Ganjar Pranowo when facing a crisis is a transformational leadership style. Ganjar Pranowo uses five things in carrying out the COVID-19 pandemic, namely 1) establishing chain-breaking policy steps, 2) avoiding top-down leadership styles, 3) promoting transparency and openness to the community, 4) using empathy in overcoming problems 5) the recovery process puts public safety first.